Foreign Relations of Kazakhstan in the Regional and Global Context: Security and Economic Aspects - KAKENOVA, Zarina; SADRI, Houman; KAKENOVA, Galina; ALPEISSOV, Amirzhan; IBRAGIMOVA, Gulnara (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The main purpose of this paper is to analyze Kazakh foreign relations in the context of global and regional powers. This work mainly focuses on the Kazakh public policy aimed at maintaining working ties with various powerful states involved in the regional affairs of Central Asia. More specifically, this paper also addresses the main sources of threat to the Kazakh state from both regional and global sources. This work discusses Astana’s efforts to decrease its traditional dependence on Moscow, as it establishes closer working ties with Washington and Beijing, as well as the capitals of major regional powers, including Tehran, Ankara, and Islamabad. The authors used comparative, system-functional, structural, and functional methods. Research results substantiated the fact that protection of the Kazakh national interests and further development of the country demands strengthening its diplomatic ties with the EU, the US, China and Russia.
Keywords: foreign relations, multi-vector foreign policy, counterbalance, independent development